Two Views on Open Innovation: Source of Dynamic Capabilities vs Threat for Corporate Stability - Yonas Ferdinand Riwu; Andi Aris Mattunruang (Foresight and STI Governance)
Small and medium-sized businesses make a significant contribution to the national GDP in both developed and developing countries. It is a constant focus of research; transformation processes take place here, which can affect a variety of socioeconomic aspects. In recent decades, open innovation and digital transformation have emerged as the emerging drivers encouraging companies to transform their business models. Their skillful combination allows players to move into a qualitatively different category. For small and medium-sized businesses, both new opportunities and complex challenges arise, which require a certain level of training and competencies.